LINGUISTIC OR EXTRALINGUISTIC REASONS FOR THE INTRODUCTION OF WORDS FROM OTHER LANGUAGES INTO THE GERMAN LANGUAGE - Rakhmanov Abdulaziz Batir ugli (Journals Park Publishing, 2023)
This article is about the introduction of words borrowed from other languages into the German language, and the factors that cause this are discussed. Also, the reasons for the introduction of appropriations and linguistic or extra-linguistic reasons, from which languages to which areas words have been appropriated, are discussed.
Keywords: political and cultural relations, scientific and technical development, Linguistics, objective reasoning, aesthetic aspect of language, German language, vocabulary.